Fat mothers' experiences of reproductive healthcare, justice, and maternal identity development : a qualitative evidence synthesis : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Albany, New Zealand - Smith, Abbie May (Massey University, 2023)
Fat people often face stigmatising experiences in reproductive healthcare; yet, much of the current scholarship is influenced by biomedical framings of fatness as problematic and does not attend to the reproductive rights of fat people. The aim of this research was to bolster the current scholarship about fat peoples’ experiences in reproductive healthcare. Using a Qualitative Evidence Synthesis approach and the Reproductive Justice framework, I thematically synthesised twenty-three primary qualitative studies related to fat peoples’ experiences of reproductive healthcare and their interaction with medical professionals. Findings indicate that interactions with medical professionals have an impact of the maternal identity development of fat people. In addition, compounding forms of intersectional difference impact upon fat peoples’ ability to access their desired reproductive healthcare experiences. Some participant enacted a range of resistance strategies in order to access their reproductive rights, and experience a positive maternal transition. Other participants were disempowered by their reproductive healthcare experiences and their maternal transition was not a positive experience. The findings have implications for future research and for medical processionals providing reproductive healthcare to fat people.
Figure 2 is reused under a Creative Commons CC BY 4.0 license.
Keywords: fat; reproductive healthcare; maternal identity; reproductive justice; qualitative evidence synthesis; 520304 Health psychology